Cardiovascular disease risk perception in a Hungarian community sample: psychometric evaluation of the ABCD Risk Perception Questionnaire - Beatrix Rafael; Béla Merkely; Tamas Martos; Márta Csabai; Zsolt Bagyura; Zsófia Ocsovszky (BMJ Open)
Objectives Reliable and valid assessment of subjective risk perception is a crucial part of cardiovascular disease (CVD) prevention and rehabilitation. Since the recently developed Attitudes and Beliefs about Cardiovascular Disease (ABCD) Risk Questionnaire complies with these requirements, the aim of the present study was to investigate the psychometric properties of the Hungarian version of the measure.Design and setting Community-based cross-sectional observational studyParticipants In sum, 410 (M=49.53 years, SD=8.09) Hungarian adults (inclusion criteria: aged 35 and above, not under treatment with a psychiatric disorder) were included in the present study (female: n=277, 67.6%; college or university-level education: n=247, 60.2%).Methods We translated the ABCD Risk Questionnaire into Hungarian and checked its psychometric properties and validity indices.Primary outcome measures Internal consistency, explorative and confirmative factorial validity. Associations with sociodemographic and health-related characteristics, as well as with measures of mental health (depressive symptoms, perceived stress and well-being).Results Exploratory and confirmatory factor analyses supported a three-factor solution, corresponding to the original subscales of Risk Perception, Perceived Benefits and Healthy Eating Intentions, with a moderate correlation between the latent constructs. The respondents’ level of knowledge on CVD risk factors was largely independent of their subjective risk perception. The results also provided evidence on the weak-to-medium associations between mental health indices and CVD-related perceptions. Based on the results, a shortened scale version was also suggested.Conclusion This study confirms the factorial structure, internal consistency and validity of the Hungarian version of the ABCD Risk Questionnaire in a non-English-speaking community sample. The ABCD Risk Perception Questionnaire is a parsimonious and psychometrically adequate measure to assess CVD-related attitudes and knowledge in the general population. Further research is needed in socioeconomically more diverse and in clinical samples, as well as in longitudinal intervention studies.